Experimental Characterization, Computational Investigation, and Structure-propertyeactivity Relationship Studies of Nickel Ferrite Nanostructures - Ali Ben Ahmed (Polytechnic)
Intending to predict the multifunctionality of Nickel ferrite in several technological and medical fields, we have prepared nickel ferrite nanostructure by coprecipitation method. X-ray Diffraction (XRD) is used to determine the crystalline structure and phase composition of materials by analyzing the pattern of X-rays scattered by the atoms within the material. Fourier Transform Infrared Spectroscopy (FTIR) provides information about a material's chemical bonds and functional groups by analyzing how it absorbs infrared light at various wavelengths. Scanning Electron Microscopy (SEM) offers high-resolution images of the material's surface morphology and texture by scanning it with a focused beam of electrons. Transmission Electron Microscopy (TEM) provides detailed images at the atomic or nanometer scale, allowing for the examination of the internal structure, crystallinity, and defects of a material. UV-visible spectroscopy measures the absorbance of ultraviolet or visible light by a material, which can give insight into its electronic structure, band gap, and optical properties. These analyses confirmed the formation of single-phase nickel ferrite nanoparticles in the range 8e14 nm. The principal quantum chemical descriptors have been analyzed and discussed. Additionally, the theoretical background of nickel ferrite was carved out using Density Functional Theory (DFT) by evaluating the electronic structure through the Frontier Molecular Orbital, Molecular Electrostatic Potential, Milliken charge distribution, Density of state spectrum, and nonlinear optical parameters embedded within the nickel ferrite molecule. Based on all these results, nickel ferrite can be considered as a multifunctional material.